2016
DOI: 10.1007/s00417-016-3274-5
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmia neonatorum treatment and prophylaxis: IPOSC global study

Abstract: We found that the incidence of ON per year per practitioner is 0-5 cases, the most common etiology is C. trachomatis, and most infants receive prophylaxis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…Ophthalmia neonatorum is a relatively common condition that can be caused by chemicals, bacteria, or viruses and affects between 1.6–12% of all newborn infants, and up to 23% of newborn infants in developing countries [ 1 – 6 ]. The prevalence of ophthalmia neonatorum varies in different parts of the world and is closely associated with socioeconomic conditions, the level of general health education, the standard of maternal healthcare, as well as the implementation of prevention programmes [ 3 – 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ophthalmia neonatorum is a relatively common condition that can be caused by chemicals, bacteria, or viruses and affects between 1.6–12% of all newborn infants, and up to 23% of newborn infants in developing countries [ 1 – 6 ]. The prevalence of ophthalmia neonatorum varies in different parts of the world and is closely associated with socioeconomic conditions, the level of general health education, the standard of maternal healthcare, as well as the implementation of prevention programmes [ 3 – 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Monocaprin is able to rapidly kill N. gonorrhoeae , N. meningitidis , and C. trachomatis [ 32 ], and has bactericidal activity against S. aureus and P. aeruginosa , making it a promising active ingredient for ocular prophylaxis and treatment to prevent the loss of vision due to eye infections. The ever-decreasing treatment options for N. gonorrhoeae [ 16 ], the rapid development of corneal melt and perforation [ 34 ], the potentially fatal consequences for N. meningitidis ocular infection dissemination [ 7 ], and the possibility of multi-species infection [ 22 ] support the development of a monocaprin-based formulation for prophylaxis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A study of the members of the American Association of Pediatric Ophthalmology and Strabismus revealed that most clinicians (85%) treated empirically [ 22 ]. It is, therefore, key that treatments are able to kill the potential causes of infant eye infections, including N. gonorrhoeae , Chlamydia trachomatis , Pseudomonas aeruginosa , and Staphylococcus aureus [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015 in Canada, the rate of reported cases of chlamydial infection in children aged less than 1 year was approximately 10 per 100000 [ 17 ]. A 2017 survey of approximately 300 pediatric ophthalmologists, primarily in North America, estimated the number of neonatal conjunctivitis cases, most commonly caused by C trachomatis , to be up to 5 per practitioner per year [ 7 ]. Because of the continued high prevalence of chlamydia worldwide and the lack of prenatal screening in certain countries, a need for safe and effective therapies for infants who acquire a chlamydial infection remains.…”
mentioning
confidence: 99%